The Supreme Court Adds New Guidelines on “Service Connection” in Determining Court-Martial Jurisdiction - Merle F. Wilberding (Washington University Law Quarterly, 1971)
In June of 1969, the Supreme Court decided O'Callahan v. Parker, and thereby rocked the very foundation of court-martial jurisdiction. Under that holding, a military court-martial had no jurisdiction to try a serviceman for a crime which occurred off-post, during off-duty hours, while he was on leave with an evening pass, and while he was in civilian clothing. In summary, Mr. Justice Douglas, writing for a 5-3 majority, concluded that courts-martial lacked jurisdiction to try servicemen, on active duty, for offenses which had no “service connection.” The underlying reasons for the O'Callahan decision were given as a constitutional interpretation that the result was necessary to preserve (a) grand jury indictments and (b) trial by peers. The Supreme Court’s pronouncement in O'Callahan of a “service connection” standard to be used in determining court-martial jurisdiction necessarily evoked a substantial amount of uncertainty as to its full meaning and extent. The military appellate courts immediately began their task of applying that standard to a great variety of factual situations. Yet, the ad hoc standard of O'Callahan needed further examination by the Supreme Court so that the Court could better explain the meaning of “service connection.” New guidelines were necessary to provide additional insight into the meaning of O'Callahan. On February 25, 1971—almost two years after the O'Callahan decision—the Supreme Court decided Relford v. Commandant, U.S. Disciplinary Barracks, which has added new dimensions in determining the scope of court-martial jurisdiction. However, to understand better the effects and implications of Relford, it is necessary first to examine the pre-Relford scope of O'Callahan as developed by the military appellate courts.
Keywords: Courts-martial; Jurisdiction